2018
DOI: 10.1039/c8tc01419a
|View full text |Cite
|
Sign up to set email alerts
|

To improve the efficiency of thermally activated delayed fluorescence OLEDs by controlling the horizontal orientation through optimizing stereoscopic and linear structures of indolocarbazole isomers

Abstract: By optimizing linear and stereoscopic structure of emitter to obtain preferential horizontal orientation, a high EQE green device of 30.0% based on IndCzpTr-2 was realized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 44 publications
3
37
0
Order By: Relevance
“…[37,38] Unexpectedly,i tw as observed that the emitting dipoles in these systemsa re partially aligneda nd that such anisotropic emission gives rise to al ight outcoupling factor.D evices with externalq uantum yields of > 30 %h ave been fabricated by using compound IndCzpTr-2 ( Figure 4). [39] However,t his process is not simplea nd, in fact, av ery recent finding from Durham University showedt hat the charge-transfer (CT) state must couple to al ocal (D or A) triplet state through spin-orbit coupling, and that the widely quoted idea of 1 CT-3 CT spinorbit coupling (SOC) interexchange is incorrect,b ecause it is a forbidden process. The ICT process of the excited molecules is affected by several environmental factors, including polarity, viscosity,a nd hydrogen-bonding interactions.…”
Section: Rtp and Df In Organic Emittersmentioning
confidence: 99%
“…[37,38] Unexpectedly,i tw as observed that the emitting dipoles in these systemsa re partially aligneda nd that such anisotropic emission gives rise to al ight outcoupling factor.D evices with externalq uantum yields of > 30 %h ave been fabricated by using compound IndCzpTr-2 ( Figure 4). [39] However,t his process is not simplea nd, in fact, av ery recent finding from Durham University showedt hat the charge-transfer (CT) state must couple to al ocal (D or A) triplet state through spin-orbit coupling, and that the widely quoted idea of 1 CT-3 CT spinorbit coupling (SOC) interexchange is incorrect,b ecause it is a forbidden process. The ICT process of the excited molecules is affected by several environmental factors, including polarity, viscosity,a nd hydrogen-bonding interactions.…”
Section: Rtp and Df In Organic Emittersmentioning
confidence: 99%
“…CzTRZ (a = 0.34) is isotropically oriented while there is almost complete horizontal orientation in TCzTRZ (a = 0.05); DACT-II is preferentially horizontally aligned (a = 0.14), and the OLED employing this emitter reached an EQE max of 29.6%. Xiang et al and Maeng et al incorporated the more planar and rigid ICz (indolocarbazole) donor in Ind-CzpTr1 and IndCzpTr2, [11] and TRZ-TPDICz, [12] respectively, achieving high EQE max values of 14.5%, 30%, and 30.3%, respectively, due in part to the preferential horizontal orientation of these emitters. Indolocarbazole has been previously employed in TADF emitter design as the donor moiety in a small number of reports, although none of these cases showed a di-functionalized ICz unit.…”
Section: Introductionmentioning
confidence: 99%
“…[6,17] By adding a second acceptor onto the ICz donor, this should lead to an increased HOMO-LUMO gap and a blue-shifted emission than the previously published mono-functionalized emitters employing the ICz moiety. [11,12,18] Indeed, ICzTRZ shows both very high photoluminescence quantum yield and strongly horizontally oriented transition dipole moments (TDMs) and demonstrates its potential in a highly efficient sky-blue OLED.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 22 ] This experiment demonstrated the benefits of the rigid donor structure along with other works about rigid donors based on carbazole. [ 23–25 ] However, the lifetime and efficiency roll‐off of the TADF devices were not satisfactory, which requires the design and development of the even stronger donor than the benzofurocarbazole.…”
Section: Introductionmentioning
confidence: 99%